(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
Gas condensate reservoirs exhibit complex thermodynamic and phase behavior, where variations in temperature significantly impact condensate dropout and overall hydrocarbon recovery. In these reservoirs, as pressure drops below the dew point, liquid condensate forms in the porous medium, reducing gas relative permeability and impairing well deliverability. Temperature changes influence phase equilibrium, interfacial tension, fluid viscosity, and retrograde condensation, making it essential to incorporate thermal effects in reservoir management and simulation models. This study presents a comprehensive analysis of the impact of temperature variations on condensate dropout and phase behavior using a combination of experimental PVT (Pressure-Volume-Temperature) analysis, numerical simulations, and thermodynamic modeling. The study integrates thermodynamic principles, phase behavior modeling, and reservoir simulation to analyze the effects of temperature fluctuations, particularly due to Joule-Thomson cooling and geothermal gradients, on reservoir performance. Results indicate that temperature variations play a critical role in condensate dropout, fluid distribution, and recovery efficiency. The findings provide valuable insights into optimizing production strategies and mitigating challenges such as condensate blockage in gas condensate reservoirs. This research highlights the importance of incorporating thermal effects in reservoir modeling and offers practical solutions for improving hydrocarbon recovery in gas condensate systems.